Multidisciplinary Management of Hepatocellular Carcinoma: Where Are We Today? - Marrero, Jorge A. (Seminars in Liver Disease, 2013)
Hepatocellular carcinoma (HCC) is the third most common cause of cancer-related death worldwide, and the incidence of HCC continues to rise. Improved understanding of risk factors for HCC has allowed the development of more effective prevention and surveillance strategies to reduce the global burden of this malignancy. Because of the complex nature of HCC, arising in a background of chronic liver dysfunction and often associated with viral infection, appropriate treatment requires a multidisciplinary approach designed to control the cancer and treat the underlying liver disease. Treatment approaches vary based on disease stage and severity, making accurate diagnosis and staging of disease critical. This has been aided by the development of new staging criteria, such as the Barcelona Clinic Liver Cancer Staging System. For earlier-stage disease, resection, radiofrequency ablation, transplantation, and transarterial chemoembolization (TACE) are preferred treatment modalities that provide optimal outcome. Until recently, few treatment options existed for patients with more advanced disease. Improved understanding of the underlying biology of the disease and the development of molecularly targeted therapies, including the multitargeted angiokinase inhibitor sorafenib, has improved outcomes in this patient population. Research into therapeutic targets and novel agents continues for more advanced disease.
Keywords: hepatocellular carcinoma; liver cancer; BCLC staging; sorafenib